(untitled) (Perioperaciina Medicina, 2025)
The issue of effective and accessible pain relief for surgical patients, including those with combat injuries and in resource-limited settings, remains highly relevant, particularly in the context of armed conflict. Since the onset of the full-scale invasion of Ukraine, the number of patients with mine-explosive injuries has significantly increased. Most of these patients are admitted to surgical departments for repeated interventions, wound dressing changes, and NPWT (Negative Pressure Wound Therapy) system replacements—procedures frequently associated with severe pain. Since 2022, inhalation analgesia with methoxyflurane (Umerox) has become available in Ukraine for the relief of pain during painful medical procedures. The aim of this study is to evaluate the effectiveness and safety of inhaled methoxyflurane (Umerox) during surgical procedures in patients with wounds managed by the open method.